Differences in Hemoglobin and Hematocrite Levels in Active Smokers and Non-Smokers - Daffa Yudhitya Nugraha; Sri Martuti; Isnin Aulia Ulfah Mu’awanah (Indonesian Journal of Global Health Research, 2026)
Hemoglobin (Hb) and hematocrit (Hct) are two important parameters in clinical hematology that reflect the body's ability to carry oxygen. Smoking is known to affect these parameters due to the exposure to carbon monoxide, which causes hypoxia and stimulates the production of more red blood cells. This phenomenon represents a significant health issue globally, including among employees in Indonesia, where smoking is common. The aim of this study is to investigate the difference in hemoglobin and hematocrit levels between active smokers and non-smokers among non-medical employees at RS Bhayangkara Tulungagung. This observational study used a cross-sectional design. A total of 30 respondents, consisting of 15 active smokers and 15 non-smokers, were selected using purposive sampling based on inclusion criteria. Data were collected through smoking behavior questionnaires and laboratory blood tests using a hematology analyzer. Statistical analysis was performed using the Shapiro-Wilk normality test and Mann-Whitney U test to examine differences between the two groups. The average hemoglobin level in active smokers was 15.98 g/dl, which was higher compared to non-smokers at 15.03 g/dl. Similarly, the average hematocrit level in smokers was 50.40%, higher than in non-smokers at 44.91%. Mann-Whitney test results indicated significant differences between the two groups for both hemoglobin (p = 0.020) and hematocrit (p = 0.004). There are significant differences in hemoglobin and hematocrit levels between active smokers and non-smokers. Active smokers tend to have higher levels of Hb and Hct as a response to the hypoxia caused by carbon monoxide exposure from cigarette smoke.